2005
DOI: 10.1049/ip-nbt:20045013
|View full text |Cite
|
Sign up to set email alerts
|

Resonant nano-cluster devices

Abstract: The resonance-enhanced absorption (REA) by metal clusters on a surface is an effective technique on which to base bio-optical devices. A four-layer device consisting of a metal mirror, a polymer or glass-type distance layer, a biomolecule interaction layer and a sub-monolayer of biorecognitively bound metal nano-clusters is reported. Experiments indicate a strong influence of the resonator homogeneity on the absorption maximum. Layer stability plays an important role in the overall performance of the device. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2008
2008

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…We found that hydrated base pairs have higher EAs than the corresponding gas-phase systems. Developments in this area have been reviewed recently. 2e,5b,8b,, DNA−metal, particularly DNA−gold, complexes appear to be good candidates for investigation of properties relevant to their use in nanobiotechnology. 2a,2d,,8b, The binding of clusters of three and six gold atoms, from the catalytic point of view of Au particles, to the individual DNA bases and Watson−Crick AT and GC base pairs employing triangular T-shaped geometries was studied recently …”
Section: Introductionmentioning
confidence: 99%
“…We found that hydrated base pairs have higher EAs than the corresponding gas-phase systems. Developments in this area have been reviewed recently. 2e,5b,8b,, DNA−metal, particularly DNA−gold, complexes appear to be good candidates for investigation of properties relevant to their use in nanobiotechnology. 2a,2d,,8b, The binding of clusters of three and six gold atoms, from the catalytic point of view of Au particles, to the individual DNA bases and Watson−Crick AT and GC base pairs employing triangular T-shaped geometries was studied recently …”
Section: Introductionmentioning
confidence: 99%
“…Plasmon resonance properties 12 of biofunctionalized Au NPs allow biodetection based on interactions with electromagnetic waves in an advanced layered optical near-field setup. If metal (Au) NPs are undergoing an antigen−antibody binding process within a defined nanodistance (≤400 nm) to a highly reflective mirror and illuminated with white light of the visible and near-infrared spectrum from the particle side, they will generate a strong color effect (REA ). This optical phenomenon was used to adjust a conventional enzyme-linked immunosorbent assay (ELISA) to a gold cluster-linked immunosorbent assay on a chip by conjugating a Au NP instead of an enzyme to the detector biomolecule .…”
Section: Resultsmentioning
confidence: 99%